2007
DOI: 10.3892/ijmm.20.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuromedins S and U and their receptors in the hypothalamus and endocrine glands of the rat

Abstract: Abstract. Neuromedin S (NMS) and neuromedin U (NMU) are regulatory peptides that share the C-terminal amino-acid sequence and act via common G protein-coupled receptors called NMUR1 and NMUR2. Semiquantitative real time-PCR showed that in the rat hypothalamus and testis NMS gene expression was markedly higher than that of the NMU gene, while the reverse occurred in the anterior pituitary and thyroid gland. Low expression of both genes was detected in the thymus, adrenal gland and ovary, whereas in the pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Our present RT-PCR and ICC studies clearly demonstrate the expression of NMUR1 as mRNA and protein in the cortex of immature rat adrenals, thereby confirming earlier findings obtained in adult animals (9,(27)(28)(29)33,34). Moreover, the detection of NMUR1 mRNA in dispersed zona glomerulosa and zona fasciculata-reticularis cells rules out the possibility that the expression was due to the presence in the specimens assayed of the non-parenchymal components of the gland (connective tissue and capillaries).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our present RT-PCR and ICC studies clearly demonstrate the expression of NMUR1 as mRNA and protein in the cortex of immature rat adrenals, thereby confirming earlier findings obtained in adult animals (9,(27)(28)(29)33,34). Moreover, the detection of NMUR1 mRNA in dispersed zona glomerulosa and zona fasciculata-reticularis cells rules out the possibility that the expression was due to the presence in the specimens assayed of the non-parenchymal components of the gland (connective tissue and capillaries).…”
Section: Discussionsupporting
confidence: 77%
“…However, the expression of NMU gene was not detected in the rat adrenals (33). Phoenix Pharmaceuticals has recently made available kits for NMU assay, that showed that this peptide may attain in human plasma concentrations of ~10 -8 M (30 pg/ml) (33). Hence, it is reasonable to conceive that NMU may activate adrenocortical NMUR1 acting as a true circulating hormone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semiquantitative real-time PCR was performed as previously detailed (22)(23)(24) in a Roche LightCycler 2.0 with software version 4.0, using the following primers: i) StAR sense (684-703), 5'-CCTGAGCAAAGCGG TGTCAT-3' and antisense (850-870), 5'-GCAAGTGGCTGG CGAACTCTA-3' (amplifon, 187 bp; accession number, NM-03155); and ii) HPRT (hypoxanthine guanine phosphoribosyl transferase 1) sense (391-412), 5'-CAGTCAACGGGGG ACATAAAAG-3' and antisense (515-536), 5'-ATTTTGG GGCTGTACTGCTTGA-3' (amplicon, 146 bp; accession number, NM-01258). The PCR program was: denaturation step at 95˚C for 10 min, 45 cycles of three amplification steps (95˚C for 10 sec, annealing at 58˚C for 5 sec, and extension at 72˚C for 10 sec), and melting curve at 60-90˚C with a heating rate of 0.1˚C/sec.…”
Section: Reverse Transcription (Rt)-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%